2016
DOI: 10.1530/joe-15-0521
|View full text |Cite
|
Sign up to set email alerts
|

The role of GPR1 signaling in mice corpus luteum

Abstract: Chemerin, a chemokine, plays important roles in immune responses, inflammation, adipogenesis, and carbohydrate metabolism. Our recent research has shown that chemerin has an inhibitory effect on hormone secretion from the testis and ovary. However, whether G protein-coupled receptor 1 (GPR1), the active receptor for chemerin, regulates steroidogenesis and luteolysis in the corpus luteum is still unknown. In this study, we established a pregnant mare serum gonadotropin-human chorionic gonadotropin (PMSG-hCG) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…It has been reported that GPR1 is expressed in metabolically active tissues and plays a functional role in glucose homoeostasis in obesity [ 30 ]. A new study from our lab shows that Chemerin and GPR1 are expressed in the mouse ovary during the estrous cycle and that Chemerin/GPR1 signaling could suppress hCG-induced progesterone synthesis and secretion during follicle development, partly through PI3K [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GPR1 is expressed in metabolically active tissues and plays a functional role in glucose homoeostasis in obesity [ 30 ]. A new study from our lab shows that Chemerin and GPR1 are expressed in the mouse ovary during the estrous cycle and that Chemerin/GPR1 signaling could suppress hCG-induced progesterone synthesis and secretion during follicle development, partly through PI3K [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Goralski et al study suggested that chemerin and CMKLR1 could regulate adipogenesis and adipocyte metabolism through ERK1/2 signaling pathway [ 54 ]. Various follicle classes have different lipid characteristics [ 55 ]; by adding GPR1 antibody and PI3K signaling inhibitor we find that the chemerin/GPR1 and PI3K signaling pathways may be involved in follicular development [ 56 ]. Therefore, GPR1 is the only known receptor for chemerin which also may regulate the follicular development through regulating follicular lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to CMKLR1, GPR1 was predominately expressed in the stromal vascular fraction of white adipose tissue, not the adipocytes ( Rourke et al, 2014 ). GPR1 mRNA was also detected in the ovaries, more precisely with high protein expression in the oocytes of developing follicles, and in the thecal cells, granulosa cells, luteal cells, and interstitial cells of the stroma ( Yang et al, 2016 ).…”
Section: Distributionmentioning
confidence: 99%
“…In mice, similar to that found in humans, chemerin mRNA was detected in a wide range of different tissues. The highest expression was seen in liver, skin, white adipose tissue, and placenta ( Goralski et al, 2007 ; Banas et al, 2015 ), but chemerin mRNA was also present in ovary, skin, lung, liver, ilieum, colon, testis, thymus, spleen, mesenteric lymph nodes, and Peyer’s patches ( Luangsay et al, 2009 ; Yang et al, 2016 ). Chemerin mRNA levels were significantly higher in white adipose tissue compared with brown, and they were more abundant in adipocytes than in the stromal vascular fraction of white adipose tissue, a similar expression pattern to its receptor CMKLR1 ( Goralski et al, 2007 ).…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation